Experience‐Driven Semantic Differentiation: Effects of a Naturalistic Experience on Within‐ and Across‐Domain Differentiation in Children. Issue 3 (20th May 2020) - Vales, Catarina; States, Sarah L.; Fisher, Anna V.
Abstract : Organized semantic networks reflecting distinctions within and across domains of knowledge are critical for higher‐level cognition. Thus, understanding how semantic structure changes with experience is a fundamental question in developmental science. This study probed changes in semantic structure in 4–6 year‐old children ( N  = 29) as a result of participating in an enrichment program at a local botanical garden. This study presents the first direct evidence that (a) the accumulation of experience with items in a domain promoted increases in both within‐ and across‐domain semantic differentiation, and that (b) this experience‐driven semantic differentiation generalized to nonexperienced items. These findings have implications for understanding the role of experience in building semantic networks, and for conceptualizing the contribution of enrichment experiences to academic success.